The negative sequence impedance as fault indicator in induction motors - Villada, Fernando; Cadavid, Diego Raúl; Aedo, José Edinson; Benavides, Bernardo Andrés; Velilla, Esteban (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
An algorithm to detect inter-turn faults in induction motors based on the negative sequence impedance is presented in this paper. The implementation through a digital prototype is also explained and its results are tested using a 3 Hp induction motor designed to induce inter-turn faults. It is concluded that the robustness of the algorithm can detect incipient faults from five turns, and it is a good tool for predictive maintenance of induction motors.